A Study on Risk & Return Analysis of Selected Industries in India - Vijayalakshmi, B. (Indian Journal of Finance, 2017)
Successful investment requires a careful assessment of the investment's potential returns and its risk of loss. A firm's risk and expected returns directly affect its share price. In real-world situations, the risk of any single investment would not be viewed independently of other assets. New investment must be considered in light of their impact on the risk and return of the portfolio of assets. In traditional financial analysis, investment management tools allow investors to evaluate the return and risk of individual investments and portfolios. Usually, higher the risk, higher the returns and lower the risk, lower the returns. However, a general understanding of this phenomenon is not sufficient to make appropriate decisions relating to investments. A more quantifiable analysis is required to understand the investment. This study reported a statistically significant positive relationship between risk and returns, both at the individual security level and at the portfolio level, confirming the theoretical predictions and empirical findings on this issue in developed markets.